2010
DOI: 10.1159/000314678
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the APOE-ε4 Allele and ACE-I/D Polymorphism on Cognition during a Two-Year Follow-Up in First-Ever Stroke Patients

Abstract: Background: Cognitive impairment is commonly observed after stroke and has a negative impact on survival and rehabilitation. Some stroke patients deteriorate in cognitive functioning whereas others do not. Environmental and demographic risk factors cannot fully explain this. There is growing evidence that a genetic predisposition plays a role in the pathogenesis of post-stroke cognitive decline. Objective: To study the influence of the APOE-Ε4 allele and the ACE-I/D polymorphism on cognitive functioning after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 139 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Another reported SNP is in the gene encoding the angiotensin-converting enzyme, one of the enzymes in the renin-angiotensin system. Studies investigating the angiotensin-converting enzyme SNP as a predictor for post-stroke cognitive decline have yielded controversial data [4852]. A genome-wide association study in the Rotterdam cohort revealed a genetic locus associated with VaD, located on the X chromosome close to the androgen receptor gene [53].…”
Section: Biomarkers and Predictors Of Psdmentioning
confidence: 99%
“…Another reported SNP is in the gene encoding the angiotensin-converting enzyme, one of the enzymes in the renin-angiotensin system. Studies investigating the angiotensin-converting enzyme SNP as a predictor for post-stroke cognitive decline have yielded controversial data [4852]. A genome-wide association study in the Rotterdam cohort revealed a genetic locus associated with VaD, located on the X chromosome close to the androgen receptor gene [53].…”
Section: Biomarkers and Predictors Of Psdmentioning
confidence: 99%
“…This effect may be stronger in the presence of APOE4 [46,50,51]. However, studies investigating ACE DD as a predictor for post-stroke cognitive decline ended with conflicting data [52][53][54][55].…”
Section: Biomarkersmentioning
confidence: 99%
“…That decline may result from the cumulative effects of additional (including otherwise clinically “silent”) cerebrovascular disease,3337 the induction of Alzheimer’s-type neuropathology by cerebrovascular disease,3841 or both of these and/or other factors 4246. This interpretation is concordant with findings from other similar studies,24,37,4749 and suggests that a single known stroke is probably understood most usefully as an overt manifestation of an underlying cerebrovascular process that in a substantial minority of individuals will result in gradual cognitive decline.…”
Section: Discussionmentioning
confidence: 99%